Advances in Industrial Robotics and Intelligent Systems - Moreira, António Paulo; Neto, Pedro; Vidal, Félix (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Robotics and intelligent systems are key technologies to promote efficient and innovative applications in the most diverse domains (industry, healthcare, agriculture, construction, mobility, etc.), performing and supporting activities that are not suitable to be performed by humans. Such activities are frequently time-consuming, repetitive tasks with low added value, which are physically demanding and/or dangerous. Nevertheless, robotics and intelligent systems face several scientific and technological challenges related to their integration and interoperability with other systems, safety, flexibility, re-configurability and autonomy. These challenges are especially relevant when robots operate in real unstructured environments and share a workspace with humans and other equipment. This reprint collects research achievements, ideas, and applications regarding advanced intelligent robotic systems, covering diverse technologies and application domains. Generically, the contributions cover optimal path-planning strategies and innovative designs for mobile manipulators, the integration of robotic and intelligent systems, grasping, manipulation, teleoperation, haptics, user experience approaches for collaborative robots, and multi-agent systems.